2012
DOI: 10.1111/j.1530-0277.2012.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Alcohol Stigma: Factor Structure and Construct Validation

Abstract: Introduction There has been an increasing interest in studying the stigma of alcohol use disorders (AUDs) yet scant research has evaluated the conceptualization and measurement of alcohol stigma. This study examined the measurement properties (i.e. factor structure) and validity of the alcohol-adapted Perceived Devaluation-Discrimination scale (PDD), which assesses the construct of perceived alcohol stigma (PAS). Materials and Methods Our sample included 34,386 respondents from the Wave 2 assessment in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…About one-sixth of the population reported experiences of discrimination, and overall mean stress and stigma scores were consistent with general population averages 55 (Table 2). A greater proportion of PLWH than those without HIV reported experiences of discrimination, and PLWH reported higher levels of perceived stress than those without HIV (Table 2; p-values both <0.05).…”
Section: Resultssupporting
confidence: 61%
“…About one-sixth of the population reported experiences of discrimination, and overall mean stress and stigma scores were consistent with general population averages 55 (Table 2). A greater proportion of PLWH than those without HIV reported experiences of discrimination, and PLWH reported higher levels of perceived stress than those without HIV (Table 2; p-values both <0.05).…”
Section: Resultssupporting
confidence: 61%
“…Current findings suggest that the presence or lack of help seeking for alcohol problems within one’s family may play a role in the evaluation of one’s own alcohol problems. It is possible that knowledge of treatment seeking for drinking among family members may bring an otherwise stigmatized issue (Glass et al, 2013a, 2013b; Keyes et al, 2010) out in the open, allowing younger persons to acknowledge their own problem drinking. Because our assessments of help seeking were based on each family member’s self-report, offspring may not have been aware of their family member’s history.…”
Section: Discussionmentioning
confidence: 99%
“…With exceptions, 39 prior studies have found women to be less likely to obtain various alcohol-related services. [40][41][42] Because the stigma of alcohol misuse [43][44][45] may be higher among women, 46 they may be more likely to under-report their alcohol use and conceal the severity of their alcohol problems.…”
Section: Discussionmentioning
confidence: 99%